Clean hydrogen production by ultrasound (sonochemistry): The effect of noble gases - Aissa Dehane; Slimane Merouani; Atef Chibani; Oualid Hamdaoui (Current Research in Green and Sustainable Chemistry, 2022)
Power ultrasonic (>100 ​kHz) splits water into free radicals and hydrogen. As a result, water sonochemistry is considered as an alternative clean and fossil-fuel-free hydrogen production technique. In this research work, the impact of rare gases (Xe, Ar, and He) on the sonochemical production of hydrogen as well as the population of active bubbles has been investigated computationally for various sonicated frequencies (213–515 ​kHz) and intensities (1–2 ​W/cm2). It has been found that both the H2 yielding and the bubble population size for H2 yielding are in the order Xe ​> ​Ar ​> ​He, whatever the imposed sonolytic parameters (i.e., frequency and power). These findings were principally ascribed to the thermal conductivity of the saturating gases, which is in the reverse order (He ​> ​Ar ​> ​Xe). Besides, the difference between Ar and Xe is condensed in comparison with the He gas. For wave frequencies larger than 213 ​kHz, however, all saturating gases (Xe, Ar, and He) behave identically, with the influence of thermal conductivity of these gases on the optimal radius muted. At 213 ​kHz, however, this impact is plainly visible (Ropt (Ar and Xe)>Ropt (He)). As per the results obtained, helium's inefficiency as a saturating gas for hydrogen production is verified, but xenon's maximal efficacy is reached when water is saturated with it. These results support the fewer experimental data reported in this emerging branch of sonochemistry, while the discussed results in the present paper (i.e., noble gases effect on sono-hydrogen production) are treated for the first time. Consequently, our work is considered as a guideline for increasing the efficacy of hydrogen production in a sonochemical reactor.